Ambliopía meridional en paciente masculino de 23 años. - Zambrano Sacón, Eliceo Ramon (2023)
Amblyopia is a neurological disorder, resulting from abnormal stimulation of the brain in the critical period of visual development. This clinical case was carried out with the objective of determining the characterization of amblyopia, based on this knowledge, to be able to provide the patient with the respective diagnosis and treatment through consultation in order to improve the quality of life. The 23-year-old male patient who comes to the optometric clinic is monitored for presenting the following symptoms such as headache, blurred vision on the side of his left eye, fatigue, eye strain when reading or browsing on his cell phone , constant tearing in the left eye. The patient states that as a 12-year-old child he was detected with astigmatism, so the treatment he was prescribed is the least invasive: the use of lenses with the necessary measurements. Apparently the indicated treatment has not been sufficient and has not been able to correctly correct the problem of astigmatism, which is why the patient is suspected of suffering from meridional amblyopia in his left eye. The diagnosis is that the patient has meridional amblyopia in his left eye that was produced by an astigmatism that was not adequately corrected in his adolescence. The patient is followed up on his treatment every two weeks for 6 months, in addition to doing simple visual exercises for approximately 15 min. After applying the follow-up to this type of therapy, an improvement in the patient's visual problem is expected.